Earnings assimilation of immigrants in Norway: A reappraisal - Pål Longva; Oddbjørn Raaum (University of Oslo, Department of Economics, 2000)
The relative earnings growth for immigrants in Norway is computed using data for all immigrants in Norway, in 1980 and 1990. We find that the earnings of OECD immigrants are comparable to those of natives at the time of entry and remain at the same level. Non-OECD immigrants earn considerably less than natives at the time of entry, but their relative earnings improve gradually over time. Also, we find that earnings of different immigrant cohorts converged from 1980 to 1990 and evidence that the rate of assimilation is non-linear. Assimilation estimates derived from cross-sectional differences between immigrant cohorts exaggerate the speed at which Non-OECD immigrants catch up with the earnings of the Norwegian born population.
Keywords: J31; 330; Wage Differentials; Earnings Assimilation; Lohn; Ausländische Arbeitskräfte; Norwegen; Migranten